Physicochemical properties, droplet size and volatility of dicamba with herbicides and adjuvants on tank-mixture - Ferreira, Pedro Henrique Urach [UNESP]; Thiesen, Leonardo Vinicius [UNESP]; Pelegrini, Gabriela [UNESP]; Ramos, Maria Fernanda Tavares [UNESP]; Pinto, Matheus Moreira Dantas [UNESP]; da Costa Ferreira, Marcelo [UNESP] (Springer Nature, 2020)
The adoption of dicamba-tolerant soybean varieties has increased the concern and demand for new drift and volatility reduction technologies. Potential spray nozzles and adjuvants should be studied to determine its effects on drift and volatility of dicamba tank-mixtures. The objective of this study was to evaluate physicochemical characteristics of spray solutions containing dicamba; to analyze droplet size effect with air induction nozzles; and to assess dicamba volatilization on soybean plants with a proposed methodology. Treatments included dicamba only and mixtures with herbicides and adjuvants. Dicamba mixed with lecithin + methyl soybean oil + ethoxylated alcohol adjuvant had the greatest efficacy potential among treatments considering tank-mixture pH, surface tension, contact angle and droplet size. The MUG11003 nozzle produced the coarsest droplet size and was better suited for drift management among nozzle types. The proposed volatilization methodology successfully indicated dicamba volatilization in exposed soybean plants and among the evaluated treatments, it showed greater volatilization for dicamba with glyphosate + lecithin + propionic acid adjuvant.